2000
DOI: 10.1017/s0029665100000604
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid metabolism in adipose tissue

Abstract: Adipose tissue is a major source of metabolic fuel. This metabolic fuel is stored in the form of triacylglycerol. Lipolysis of triacylglycerol yields non-esterified fatty acids and glycerol. In human subjects in vivo studies of the regulation of lipid metabolism in adipose tissue have been difficult because of the heterogeneous nature of the tissue and lack of a vascular pedicle. In the last decade the methodology of study of adipose tissue has improved with the advent of the anterior abdominal wall adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Energy intake is mainly dependent on food ingestion and energy expenditure depends on several factors, including exercise and heat production, or so-called adaptive thermogenesis. Brown adipose tissue (BAT) is the major site for adrenergic mediated adaptive thermogenesis involving the uncoupling protein-1 (UCP1), whereas white adipose tissue (WAT) is mostly implicated in the regulation of lipid storage and catabolism [118, 119]. Previous study showed that basal gene expression of UCP1 and PGC-1α was increased in BAT of SHP −/− mice and this was associated with increased oxygen consumption, heat production and decreased obesity, indicating that SHP may be a negative regulator of energy utilization [120].…”
Section: Shp In Metabolismmentioning
confidence: 99%
“…Energy intake is mainly dependent on food ingestion and energy expenditure depends on several factors, including exercise and heat production, or so-called adaptive thermogenesis. Brown adipose tissue (BAT) is the major site for adrenergic mediated adaptive thermogenesis involving the uncoupling protein-1 (UCP1), whereas white adipose tissue (WAT) is mostly implicated in the regulation of lipid storage and catabolism [118, 119]. Previous study showed that basal gene expression of UCP1 and PGC-1α was increased in BAT of SHP −/− mice and this was associated with increased oxygen consumption, heat production and decreased obesity, indicating that SHP may be a negative regulator of energy utilization [120].…”
Section: Shp In Metabolismmentioning
confidence: 99%
“…SREBP1 facilitates lipogenesis by induction of extracellular lipolytic enzyme (lipoprotein lipase) and lipogenic enzyme (fatty acid synthase) that in turn, lead to an increase in fatty acid uptake and synthesis, promoting lipid accumulation within the adipocyte [58,59]. The release of free fatty acid from adipocytes is facilitated by an intracellular lipolytic enzyme, hormone-sensitive lipase [60]. …”
Section: Catch-up Growth and Fat Accrualmentioning
confidence: 99%
“…Whereas energy intake is solely dependent on food ingestion, energy expenditure depends on several factors, such as exercise and heat production, or so-called adaptive thermogenesis. Despite extensive research focused on the understanding of obesity, the molecular mechanisms underlying increased adiposity are not fully understood.Brown adipose tissue (BAT) is the major site for adrenergic mediated adaptive thermogenesis involving the uncoupling protein-1 (UCP1), whereas white adipose tissue (WAT) is mostly implicated in the regulation of lipid storage and catabolism (8,13,15,26). Adaptive thermogenesis allows rodents to slow the development of obesity when overfed and maintain body temperature when exposed to a cold environment.…”
mentioning
confidence: 99%